Rancang Bangun Alat Pengukur Sifat Fisis air Berbasis Arduino - Della, Yogi; Suppa, Rinto; Dani, Ahmad Ali Hakam (JTIK (Jurnal Teknik Informatika Kaputama), 2021)
The purpose of this study was to design and build an Arduino-based Water Physical Properties Measurement Tool in Sumpira Village. the use of this tool helps the people of Sumpira village to test the pH and NTU values of the water they have consumed so far. This tool uses 2 sensors namely a pH sensor and an NTU sensor, the results of which will be displayed on the 16x2 type LCD. The research method in this thesis includes analysis, designing tool design, testing and implementation. In designing the arduino-based water physical properties meter, Arduinouno type Atmega328 and Arduino mega type Atmega2560 are needed to control the pH sensor and the NTU sensor as a measure of water value properties and some of the components needed in designing the measurement of the physical value of water, including LCD type 16x2 , breadboard, and the on off button. Based on the tests that have been carried out, it can be concluded as follows: This equipment can be tested and can be used to help people determine the feasibility level of the water they consume so far. The results of field testing can be proven by comparing the results of testing this tool at PDAM BUKAE Masamba with only 0.1% ratio, so it can be said to meet the standard of feasibility.